Mutant B3GALT6 in a Multiplex Family: A Dominant Variant Co-Segregated With Moderate Malformations - Shen, Fang; Yang, Yongjia; Zheng, Yu; Tu, Ming; Zhao, Liu; Luo, Zhenqing; Fu, Yuyan; Zhu, Yimin (Frontiers in Genetics, 2022)
B3GALT6 is a well-documented disease-related gene. Several B3GALT6-recessive variants have been reported to cause Ehlers–Danlos syndrome (EDS). To the best of our knowledge, no dominant B3GALT6 variant that causes human disease has been reported. In 2012, we reported on a three-generation, autosomal-dominant family with multiple members who suffered from radioulnar joint rotation limitation, scoliosis, thick vermilion of both lips, and others, but the genetic cause was unknown. Here, exome sequencing of the family identified mutant B3GALT6 as the cause of the multiplex affected family. We observed that, in the compound heterozygous pattern (i.e., c.883C>T:p.R295C and c.510_517del:p.L170fs*268), mutant B3GALT6 led to severe consequences, and in the dominant pattern, an elongated B3GALT6 variant co-segregated with moderate phenotypes. The functional experiments were performed in vitro. The R295C variant led to subcellular mislocalization, whereas the L170fs*268 showed normal subcellular localization, but it led to an elongated protein. Given that most of the catalytic galactosyltransferase domain was disrupted for the L170fs*268 (it is unlikely that such a protein has activity), we propose that the L170fs*268 occupies the normal B3GALT6 protein position in the Golgi and exerts a dominant-negative effect.